Contemporaneous Emotion Regulation Theoretical Models: A Systematic Review - Cremades, Camila Florencia (2022)
Background: Emotions and their regulation are a phenomenon present in everyday life. Despite its relevance and growing interest, a consensual and univocal definition has not yet been reached. Objective: This paper aims to review contemporary theoretical models of emotion regulation, looking for agreements and divergences between authors. It seeks to identify the main processes considered when working with emotional dysregulation. Method: Our team conducted a systematic review in the form of a narrative synthesis following the guidelines of the PRISMA statement. The database used were SCOPUS, PUBMED, and Dialnet. We included articles published between 2018 and 2020, which have been peer-reviewed in indexed scientific journals, whose central theme was the theoretical presentation of the construct of emotional regulation. We excluded articles that conceptualized only one dimension of the construct focused on specific populations and empirical studies without a theoretical conceptualization of the construct. The information was systematized in a table identifying authors' information, country of institutional affiliation, main characteristics of the given definition of emotion regulation, regulation skills mentioned, and underlying theoretical frameworks. Results: We identified ten different theoretical frameworks that propose models of emotion regulation. The main components found in the definition were the complexity of the construct, goal orientation, intra- or interpersonal regulation, the proposal of moderators, and its voluntary character. Discussion: There is a consensus on the use of emotion regulation strategies to adapt to environmental demands, achieve goals and increase well-being. We identify that people's learning history is an important factor in the development of emotional regulation skills. In addition, context and personality traits are proposed as moderators of the therapeutic efficacy of interventions focused on emotional regulation. Further studies along these lines would favor the implementation of preventive interventions and the personalization of treatments.